Does ecological accountability restrain the financialization of heavily polluting enterprises? Evidence from China - Wang, Weida; Zhao, Chuanyang; Ning, Jinhui; Yin, Shi; Zhang, Dongyan (Frontiers in Environmental Science, 2024)
Ecological accountability is an important means for the Chinese government to promote the development of green policies. In this study, a central environmental protection inspection was used as an exogenous shock event, China's A-share-listed companies were selected as the research sample, and the impact of the central environmental protection inspection on the financialization behavior of heavily polluting enterprises was empirically tested. The research shows that the central environmental protection inspection significantly inhibited the financialization of heavily polluting enterprises. A mechanism analysis showed that the central environmental protection inspection mainly inhibited the financialization of enterprises by promoting green innovation, which shows that the implementation of a central environmental protection inspection can promote green innovation and transformation by forcing heavily polluting enterprises to return to their main business, produce a "crowding-out effect" on financial assets, and place a focus on sustainable and high-quality development. A heterogeneity test showed that the inhibitory effect of the central environmental protection inspection on enterprise financialization was more significant in the sample group of state-owned enterprises and areas with a higher level of development of green finance. This study provides a reference for evaluating the implementation effect and effectiveness of central environmental protection inspections and has significance for regulatory authorities in improving the revision of ecological accountability policies, promoting the green transformation of heavy pollution industries, and regulating the financial asset investment behavior of listed companies.